Racial Discrimination in Novel We Cast A Shadow (2019) by Maurice Carlos Ruffin - Ritma Ritma; Leni Marlina (Universitas Negeri Padang, 2021)
AbstractThis study is aimed to seek how far the novel of We Cast A Shadow (2019) by Maurice Carlos Ruffin reflected the issues of racial discrimination. Racial discrimination refers to the character who face discrimination through mistreatment and violence that make a great impact in the future. The unnamed character had been through a difficult time since he was a child. This analysis is related to the postcolonial theory proposed by Pieterse and Powell (2016). The use of theory was based on the interpretation in the text and context of the novel. The data was collected from the quotation in the novel. The data collection was in the form of sentences and paragraphs. This research was a descriptive and content analysis study. The result of the study shows that the racial discrimination of African-American character can be seen through violence to African-American and arbitrary Policy on Economic Aspect. In conclusion, in this post-civil rights movement era, African-Americans still face racial discrimination.